PENGEMBANGAN MEDIA PEMBELAJARAN MODUL ELEKTRONIK MATA KULIAH DIAGNOSIS KENDARAAN DI PROGRAM STUDI PENDIDIKAN TEKNIK MESIN UNIVERSITAS SRIWIJAYA - Lery Rahmatullah Siregar; harlin harlin; Imam Syofii (UNIVERSITAS SRIWIJAYA, 2017)
This research is a research & development (R & D). This study aims to produce instructional media electronics module subjects Diagnosis Vehicle programmed study Mechanical Engineering Education Sriwijaya University in the form of electronic media learning valid and practical serts have a potential effect, then that would be applied as a medium of learning both on campus and outside campus. The research location is programmed study Mechanical Engineering Education sriwijaya university in the academic year 2016/2017 in 2014 Inderalaya students. Media validity was assessed by two experts, namely, validation matter experts and media experts. The validity of the material to get 87.96% of the categorized results are very valid, the validity sedangan media get 85% were categorized as very valid too. Followed by a one to one interview, in which the comments of the media is very positive, the next to see the practicality do small group stage, the result is 83.84% of the results included practical. , In the field test results received n-gain of 0.90 and in the high category. It can be concluded that the electronic module Vehicle Diagnosis is valid, practical, and have a potential effect.